Leadership, religiousness, state ownership of an enterprise and unethical pro-organizational behavior: The mediating role of organizational identification. - Tomasz Gigol (Public Library of Science (PLoS), 2021)
This study proposes a model in which organizational identification mediates the correlations among state-owned enterprises (SOEs), authentic leadership, Christian religiousness, and unethical pro-organizational behavior (UPB). The proposed theoretical framework is based on moral identity theory, social identity theory, and social exchange theory. We tested the hypothesized model using data (N  =  389) from employees of various companies and industries in Poland. Of the respondents, 49.1% worked in SOEs. The reliability and validity of the measures were established. The correlation coefficients among the analyzed variables were obtained using the bootstrap confidence interval method. To thoroughly examine the causal relationships among the variables, covariance-based structural equation modeling (CB-SEM) was adopted. Path analysis was conducted and used to verify a model in which organizational identification mediated the correlations among state involvement in the ownership of an enterprise, authentic leadership, Christian religiousness, and UPB. State involvement in the ownership of an enterprise, authentic leadership, and Christian religiousness were linked to increased organizational identification, which in turn was linked to the intensification of UPB. With the level of organizational identification controlled, state ownership of an enterprise was linked to lower UPB intensity. Limitations, implications and future research directions are discussed.